CURRENT ISSUES OF OBESITY CLASSIFICATION - I. V. Samorodskaya; E. V. Bolotova; S. A. Boytsov (Кардиоваскулярная терапия и профилактика)
The main aim of the review is analysis of recent obesity classifications, taken from the viewpoint of cardiovascular diseases (CVD) risk stratification and metabolic diseases, evaluation of the complication risk and long-term prognosis (mortality). Novel obesity classification of AACE/ACE (2014) concentrates the attention on and makes it to begin multifactorial weight correction for the persons with the highest risk of complication development and worsening of the health state. However, in time deficiency conditions of the primary healthcare physician's practice, and necessity of additions for the screening programmes, usage of the classification is problematic. Recently there is no convincing evidence for that BMI 25-35 kg/m2 without mention of metabolic changes, waist circumference (WC), fat-muscle ration, is itself a risk factor (FR) of higher cardiovascular mortality (comparing to normal BMI) in long-term prognosis. Recently there is a row of metabolically healthy obesity (MHO) definitions which use different criteria for the evaluation of healthy metabolism. Hence further studies shall focus on the development of unified MHO definition and selection of groups that are at the most risk of CVD and metabolic diseases.